Relationship of taste recognition thresholds with body mass index, food consumption and perception of selected Filipino women - Bularin, Abigail M.; Villarino, Blanca J. (2006)
ABSTRACT The study was conducted to investigate the relationship of recognition thresholds of the 5 basic tastes namely: sweet, salty, umami, sour and bitter, of selected Filipino women with their Body Mass Index (BMI), food consumption and perception. Fifty-one female panelists were recruited, and were classified as underweight, normal and overweight based on their BMIs. Taste recognition thresholds for the basic tastes were measured using increasing concentrations (geometric series) of aqueous solutions of food substances evoking the tastes. Panelists also completed a food questionnaire in which frequency of consumption, taste and health perceptions of 35 food items representing the food groups in the Filipino Food Pyramid were rated. The BMI of the respondents ranged from 16.96 to 29.9 kg/m^2. One-way Analysis of Variance (ANOVA) of the group thresholds for the basic tastes showed no significant (p>0.05)differences across BMIs. Pearson's Product-Moment Correlation coefficients for all variables fell within the range of -0.3 to 0.3, showing little or no association between the recognition thresholds of the participants and their BMIs and demographic characteristics. Spearman's Rank Correlation coefficient obtained (-0.47 to 0.59), indicate a weak to moderate relationship of BMI, age and taste recognition thresholds of the respondents with their food consumption and perception.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Taste -- Psychological effect; Food consumption -- Philippines; Tastes and sensations